2014
DOI: 10.1002/14651858.cd009177.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmacological interventions for chronic pain in people with spinal cord injury

Abstract: Non-pharmacological interventions for chronic pain in people with spinal cord injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
155
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(158 citation statements)
references
References 67 publications
2
155
1
Order By: Relevance
“…Fregni et al 30 have shown that five days of anodal CCTS in M1 decreases patients' pain without interfering with the neuropsychological condition or being associated to the presence of anxiety and depression. Two recent meta-analyses have shown that anodal CCTS in M1 has moderate analgesic effect on spinal cord injury pain 31,32 . The review of Boldt et al 31 has also involved other noninvasive neuromodulatory resources such as rTMS and acupuncture, which however have not shown effect on these patients' pain.…”
Section: Physical Rehabilitation For Neuropathic Pain After Central Nmentioning
confidence: 99%
See 2 more Smart Citations
“…Fregni et al 30 have shown that five days of anodal CCTS in M1 decreases patients' pain without interfering with the neuropsychological condition or being associated to the presence of anxiety and depression. Two recent meta-analyses have shown that anodal CCTS in M1 has moderate analgesic effect on spinal cord injury pain 31,32 . The review of Boldt et al 31 has also involved other noninvasive neuromodulatory resources such as rTMS and acupuncture, which however have not shown effect on these patients' pain.…”
Section: Physical Rehabilitation For Neuropathic Pain After Central Nmentioning
confidence: 99%
“…Two recent meta-analyses have shown that anodal CCTS in M1 has moderate analgesic effect on spinal cord injury pain 31,32 . The review of Boldt et al 31 has also involved other noninvasive neuromodulatory resources such as rTMS and acupuncture, which however have not shown effect on these patients' pain.…”
Section: Physical Rehabilitation For Neuropathic Pain After Central Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, it is important to note that a recent Cochrane Database Systematic Review has found that there is still insufficient evidence for the use of non-pharmacologic interventions (i.e., tDCS, TMS, exercise programs, acupuncture, and others) in the treatment of neuropathic chronic pain, at least in spinal cord-injured patients (Boldt et al 2011). It is also important to note that the conclusion in Boldt et al (2011) is not that these interventions are ineffectual, but that more research with randomized control protocols, adequate sample sizes, and sensitive methods to evaluate outcomes are needed. We fully agree with these conclusions and would like to suggest the same for each of the specific research fields reviewed here.…”
Section: Painmentioning
confidence: 99%
“…Despite the prognostic significance of diminished conscious pain perception in canine SCI, routine clinical evaluation of dogs with SCI has historically focused on locomotor scoring and only a crude assessment of the ‘presence’ or ‘absence’ of a behavioral response to a painful stimulus (Olby et al, 2001; Levine et al, 2009; Lascelles, 2013). Abnormalities in sensory processing such as allodynia and hyperesthesia are reported in up to 90% of human patients after SCI (Boldt et al, 2014). Sensory abnormalities have yet to be thoroughly explored in dogs with SCI, despite being repeatedly documented in rodent models of SCI and in the human clinical setting (Carlton et al, 2009; Felix et al, 2009; Densmore et al, 2010; Lindsey et al, 2010; Hoschouer et al, 2010; Hayes et al, 2012).…”
Section: Introductionmentioning
confidence: 99%